Kinetics and Mechanism of Protein Tyrosine Phosphatase 1B (PTP1B) Inactivation by Acrolein - Seiner, Derrick R. (2007)
Human cells are exposed to the electrophilic α,β-unsaturated aldehyde acrolein from a variety of sources. Reaction of acrolein with functionally critical protein thiol residues can yield important biological consequences. Protein tyrosine phosphatases (PTPs) are an important class of cysteine-dependent enzymes whose reactivity with acrolein previously has not been well characterized. These enzymes catalyze the dephosphorylation of phosphotyrosine residues on proteins via a phosphocysteine intermediate. PTPs work in tandem with protein tyrosine kinases to regulate a number of critically important mammalian signal transduction pathways. We find that acrolein is a potent time-dependent inactivator of the enzyme PTP1B (k(inact) = 0.02 ± 0.005 s(−1), K(I) = 2.3 ± 0.6 × 10(−4) M). Enzyme activity does not return upon gel filtration of the inactivated enzyme and addition of the competitive phosphatase inhibitor vanadate slows inactivation of PTP1B by acrolein. Together these observations suggest that acrolein covalently modifies the active site of PTP1B. Mass spectrometric analysis reveals that acrolein modifies the catalytic cysteine residue at the active site of the enzyme. Aliphatic aldehydes such as glyoxal, acetaldehyde, and propanal are relatively weak inactivators of PTP1B under the conditions employed here. Similarly, unsaturated aldehydes such as crotonaldehyde and 3-methyl-2-butenal bearing substitution at the alkene terminus are poor inactivators of the enzyme. Overall, the data suggest that enzyme inactivation occurs via conjugate addition of the catalytic cysteine residue to the carbon-carbon double bond of acrolein. The results indicate that inactivation of PTPs should be considered as a possible contributor to the diverse biological activities of acrolein and structurally-related α,β-unsaturated aldehydes.